Post-COVID urban-rural difference in prevalence, patterns and predictors of self-medication: A cross-sectional study from Kerala - Nayana Raj; Teena Mary Joy; Jeby Jose Olickal; Kavumpurathu Raman Thankappan (Elsevier, 2024)
Introduction: The COVID-19 pandemic led to restrictions on healthcare services, causing people to resort to self-medication without professional guidance. This study aimed to assess the self-medication practices in rural and urban areas of Ernakulam district, India exploring the prevalence patterns and predictors. Methods: In this cross-sectional study was done from January to July 2023 among adults aged>=18 years using multistage cluster sampling, 400 urban and 240 rural participants were surveyed. Data were collected using a pre-tested structured interview schedule on demographics and three months of self-medication details. Binary logistic regression analysis was done to find out the factors associated with self-medication. Results: Self-medication prevalence was 56.9 % [95 % confidence interval (CI) 50.7-58.6 %], higher in rural (61.3 %, 95 % CI 54.8-67.4 %) than urban areas (50.8 %, 95 % CI 45.7-55.8 %). Fever was the primary symptom for rural self-medication (44.8 %), and headache (36 %) in urban areas (36 %). Challenges in accessing doctors led participants to self-medicate; pharmacies were the main source, and commonly used medications were antipyretics and analgesics. Adults aged≤48 years (aOR 2.31, 95 % CI 1.22-4.35, p = 0.010), those who were married (aOR 3.11, CI 1.54-6.26, p = 0.001), and belonging to below poverty line (aOR = 8.03, 95 % CI 3.14-20.54, p < 0.001) were more likely to report self-medication compared to their counter parts in rural areas. In urban areas, only younger age (aOR 3.13, 95 % CI 1.78-5.50, p < 0.001) was significant. Conclusion: More than half of the participants in urban and rural areas reported self-medication in our study. Efforts are warranted to reduce self-medication practices in the community.